Stem-cell therapy via gastroscopy improves the outcome of esophageal anastomotic leakage - Hu, Yannan; Chu, Heng; Xue, Xiang; Yan, Yan; Chen, Wenbang; Lang, Xilong; Zhang, Hao (Frontiers in Oncology, 2022)
Background Esophageal anastomotic leakage (EAL) is a severe complication usually occurring after esophagectomy. Although there are various therapeutic methods for EAL treatment, they have not achieved satisfactory results. A previous study showed that the combination of mesenchymal stem cells (MSCs) and fibrin scaffold (FS) can treat EAL. This study aimed to evaluate the efficacy of the injection of MSCs and FS through a new engraftment gastroscope for EAL treatment. Methods Twelve adult pigs were randomly divided into the MSCs group (n = 6) and control group (n = 6). A stomach tube was then inserted through the leakage to construct the EAL model, which was removed after one week. The combination of MSCs and FS was autografted at the EAL site for pigs in the MSCs group using the tailor-made gastroscope while only FS was autografted for the pigs in the control group. Local status of EAL was evaluated using gastroscopy. Histological analyses and western blot (WB) were used to assess the gross specimens of esophagi around EALs. Results Gastroscopy showed a higher closure rate and a lower infection rate in the MSCs group than in the control group. However, the mortality was not significantly different between the two groups. HE staining showed a severe inflammatory response with dispersive infiltration of inflammatory cells and unhealed leakage in the control group. However, the infiltration of inflammatory cells was not altered in the MSCs group, and the leakage was completely healed. WB analyses showed that Myogenin and α-SMA expressions were significantly higher in the MSCs group than in the control group. Conclusion A porcine model of EAL was successfully developed by accessing the transplantation site through the esophagus. Further data revealed that the implantation of MSCs in FS via the novel engraftment gastroscope can promote the repair and occlusion of EAL. Therefore, the proposed method is a promising strategy for EAL treatment.